An algorithm to calculate interfacial area for multiphase mass transfer through the volume-of-fluid method. (September 2016) - Soh, Gim Yau; Yeoh, Guan Heng; Timchenko, Victoria
Highlights: Algorithm to find interfacial area for mass transfer within volume-of-fluid (VOF). Test cases show algorithm can calculate multiphase interfacial area correctly. Algorithm proven to simulate mass transfer more accurately. Superior to the standard |∇ α | method for mass transfer area approximation. Abstract: Mass transfer occurs in many simple and complex processes. As mass transfer persists across the interface separating immiscible fluids, the proper determination of the interfacial area is critical in accurately capturing the mass transfer process. In this paper, an algorithm is proposed and developed whereby the interfacial area is ascertained within the framework of the volume-of-fluid (VOF) multiphase model. The algorithm is based on a concept similar to the Piecewise-Linear Interface Calculation (PLIC) method where a plane cutting an orthogonal mesh cell is considered. Through this algorithm, the interfacial area can be approximated as the area of the resulting polygon from the plane cut. A series of test cases are conducted to verify the accuracy of the algorithm. The results indicate that the algorithm is able to correctly calculate the interfacial area of multiphase systems including for complex cases such as droplets in microchannels. The algorithm is also shown to simulate mass transfer accurately and is demonstrated to be superior to the standard | ∇ α | function, which is used widely in literature to approximate the interfacial area in VOF simulations.